The Influence of Liquidity, Leverage, Activity, Profitability, Company Size, and Net Profit Margin on Financial Performance (Case Study of Manufacturing Companies Listed on Idx in the Years 2018 – 2020) - Fanni Jovita*; Bayu Wulandari; Elisabeth Elisabeth; Mhd Zulkifli Hasibuan (Universitas Syiah Kuala, 2023)
This research examines manufacturing companies listed on the IDX in 2018-2020. This study uses a quantitative research type using secondary data taken from the annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The number of samples in this study were 99 samples, using a multiple linear regression model. The result is that the Liquidity Variable has no significant effect on Financial Performance, Leverage Variable has a significant effect on Financial Performance, Activity has a significant effect on Financial Performance, Profitability Variable has a significant effect on Financial Performance, Company Size Variable has no significant effect on Financial Performance. The variables of Liquidity, Leverage, Activity, Profitability and Company Size have a simultaneous effect on Financial Performance.